2016
DOI: 10.1115/1.4033033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cerium on the Deformation and Corrosion of Magnesium

Abstract: In this study, a new magnesium (Mg) alloy containing 0.4% Ce was developed using the technique of disintegrated melt deposition followed by hot extrusion. The tensile and compressive properties of the developed Mg–0.4Ce alloy were investigated before and after heat treatment with an intention of understanding the influence of cerium on the deformation and corrosion of magnesium. Interestingly, cerium addition has enhanced the strength (by 182% and 118%) as well as the elongation to failure of Mg (by 93% and 8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The microhardness of Mg-3Al-0.4Ce alloy is seen to be much higher as compared to that of pure Mg [5] and commercially available AZ31B [11]. This is due to the addition of a rare earth element.…”
Section: Microhardnessmentioning
confidence: 86%
See 1 more Smart Citation
“…The microhardness of Mg-3Al-0.4Ce alloy is seen to be much higher as compared to that of pure Mg [5] and commercially available AZ31B [11]. This is due to the addition of a rare earth element.…”
Section: Microhardnessmentioning
confidence: 86%
“…Furthermore, the solubility of RE metals in Mg is not very high, hence, increase in the content of solute RE concentration reduces strength [4]. The results of literature studies showed that the addition of 0.4% Ce [5] yields the best properties of tensile strength and ductility and no research has been done to study the effect of reinforcement on Mg-Al-Ce alloys. Furthermore, reinforcement with nano-particulates is also another possibility to improve the properties of Mg.…”
Section: Introductionmentioning
confidence: 95%
“…The secondary phases (Mg 17 La 2 ) were segregated and distributed discontinuously across grains (see Figure 2c,d). Mg 17 La 2 phase had a size of about 1 ± 0.5 µm unlike Mg 17 Ce 2 phase in Mg-0.4Ce alloy whose size was much lower than 1 µm [6]. Further, it is also interesting to note that the Mg 17 La 2 secondary phases with a much higher volume fraction of~0.46 as compared to Mg 17 Ce 2 phase in Mg-0.4Ce alloy (vol.…”
Section: Microstructural Characterizationmentioning
confidence: 94%
“…The Rare Earths were added in the form of master alloys (Mg-30%RE) with >99% purity obtained from Sunrelier Metal Co. Limited, Pudong, Shanghai, China. Mg-4La-0.4Ce alloy was synthesized using the Disintegrated Melt Deposition technique [6]. The ingot obtained from casting was machined and soaked at 400 • C for 1 hour in a constant temperature furnace before extrusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation